Minor fishery for the Indian oil sardine (Sardinella longiceps) along Saurashtra coast - Gopal, C; Savaria, Y D (Indian Journal of Fisheries, 2011)
Major landings of oil sardine in India are fiom the southwestcoast(Anthony Raja 1969, Anonymous \9M). FotedarandSavaria(1988) reported oil sardine landings along the Saurashtra Cbast during November 1986 - February 1987. The present study was conducted to know whether the oil sardine occurs regularly along the Saurashtra coast